Pengaruh Kemampuan Penguasaan Mekanika Teknik Terhadap Kemampuan Mahasiswa Menyelesaikan Perhitungan Konstruksi Beton Pada Program Studi Teknik Sipil Fakultas Teknik UNIMA - Tulaka, Titof (Peneliti.net, 2024)
The purpose of this study was to determine the relationship between the use of workshops with student learning achievement in the subject of theory and work practice with student learning achievement in the subject of theory and practice of door and window frame work of students majoring in building at SMK Negeri 3 Tondano. The technique used in data collection is to use a questionnaire in the form of a questionnaire and distributed to students to obtain data on the use of workshops and documentation to obtain student learning outcomes in the subject of door and window frame work, in this study student learning outcomes are student report card scores. The results through student learning achievement at SMK Negeri 3 Tondano can be grouped into 3 categories, namely high scores, medium scores and low scores. Where high scores are 30%, medium scores are 20% and low scores are 50%. This shows that the learning achievements achieved by students at SMK Negeri 3 Tondano are still lacking.